2003
DOI: 10.1089/10763270360728099
|View full text |Cite
|
Sign up to set email alerts
|

Healing of Artificial Fenestration Defects by Seeding of Fibroblast-Like Cells Derived from Regenerated Periodontal Ligament in a Dog: A Preliminary Study

Abstract: The purpose of this study was to assess the seeding of fibroblast-like cells to promote periodontal healing in artificial fenestration defects in a dog. Fibroblast-like cells were cultured by incubating regenerated periodontal ligament tissue, that had been surgically taken, underneath a Teflon membrane. Fenestration defects were surgically induced on the maxillary canine and first molar teeth at a spacing of 5 to 5 mm. Passage 4 cells (2 x 10(5) cells) in autologous blood coagulum were placed on root surfaces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 31 publications
0
45
0
Order By: Relevance
“…In addition, the scaffold must be able to maintain a space within the wound site for the cells to grow into (5). Although using soft scaffolds such as hydro gels or collagen sponge has been the predominant strategy (8,20,29,42,54,64), the applications of these soft scaffolds are limited due to their poor mechanical properties. Solid scaffolds such as hydroxyapatite/tricalcium phosphate (HA/TCP) provide improved support for periodontal tissue regeneration (7,33).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the scaffold must be able to maintain a space within the wound site for the cells to grow into (5). Although using soft scaffolds such as hydro gels or collagen sponge has been the predominant strategy (8,20,29,42,54,64), the applications of these soft scaffolds are limited due to their poor mechanical properties. Solid scaffolds such as hydroxyapatite/tricalcium phosphate (HA/TCP) provide improved support for periodontal tissue regeneration (7,33).…”
Section: Discussionmentioning
confidence: 99%
“…Transplantation of cells derived from the periodontal ligament has showed the potential to regenerate periodontal attachment structures in vivo (Lekic et al, 2001;Dogan et al, 2003;Nakahara et al, 2004;Akizuki et al, 2005;Hasegawa et al, 2005). Cementoblasts or tooth-lining cells have a marked ability to induce mineralization in an ex vivo model (Jin et al, 2003b) and in vivo in periodontal wounds .…”
Section: (44) Cell-based Therapies In Periodontal Tissue Engineeringmentioning
confidence: 99%
“…Previous studies that reported the regenerative properties of PDL using animal models indicated the existence of stem cells in PDL tissue [3, 4]. Liu et al reported that autologous PDL-MSCs enhanced regeneration of periodontal tissue, including alveolar bone, cementum and PDL in a minipig [5].…”
Section: Current Progress In Periodontal Cell Transplantation Therapymentioning
confidence: 99%